Research on metallothionein of the freshwater mussel Cristaria bialata - Binh, Doan Viet; Kim Dung, Nguyen Thi; Chi, Phan Van (Academia Journal of Biology, 2014)
Metallothionein is a cytoplasmic protein witch may serve a detoxication function or as a storage/transport protein for essential trace metals in animals. Metallothionein of bivalve molluscs are often used for evaluation of heavy metal environmental pollution. In this article we report about our fist results on research of metallothionein of the freshwater mussel (Cristaria bialata). The induction of metallothionein was carried out in experiment with exposure to CdCl2. The mussel were kept in a 80L aquaria with aerated freshwater contaminated with 15 mgCd2+/l. The water in aquaria was changed two times a week. The mussel were fed every two days with a small amount of fresh diatoms or spirulina. They were transferred into fresh medium every second week. Contents of metallothionein were analyzed by the Cd/Hemoglobin affinity assay. The determinated values of metallothionein are 128.87 (after 21 days) and 202.68 mg/g wet weight (after 35 days). Metallothionein was isolated from the digestive gland of the mussel by gel filtration chromatography with Sephadex G-75. Fractions were monitored for absorbance at 254 and 280 nm by UV spectrophotometer and showed higher absorbance at 254 then at 280 nm. Cadmium content of the fractions was analyzed by atomic absorption spectrometry. The Cd2+-containing peak fractions were pooled, lyophilized and further purified by ion exchange chromatography with DEAE-cellulose. The elution profiles of the fractions showed 2 isoforms of metallothionein. The determinate value of the molecular weight of metallothionein of the freshwater mussel is 18,5 kDa. Metallothionein of the freshwater mussel (Cristaria bialata) could be propose to use as biomarker for water pollution heavy metal (Cadmium).